Implementación de un sistema de contabilidad de costos por órdenes de producción en la fábrica procesadora de productos lácteos Ecualac ubicada en la parroquia Machachi, cantón Mejía, provincia Pichincha en el periodo de enero a junio 2013 - Camacho Simbaña, Jenny Margoth (2015)
This thesis was developed at the Dairy Industry: "ECUALAC", in which it was determined that the main problem affecting their financial, economic and production mainly for lack of a proper system of cost activities; for this reason it impossible to know exactly their real manufacturing costs. Through a preliminary study; and by applying techniques and statistical methods such as interviews and surveys directed to the head of production, management, customers and suppliers of the company they were allowed to know the current situation of the organization and has concluded that it must implement the system Costs Orders production; this system enabled the company to more accurately determine the real costs incurred for the development of a product and have a productive enhancement and improvement of the system current job, a more efficient production process is also managed, trying to have control over production costs, has been obtained also important information for making decisions.